Pengaruh pengalaman dan keterampilan dalam mencapai kesuksesan belajar - Farikha, Tsania Nur (Maliki Interdisciplinary Journal, 2024)
That success in learning is a subjective success that is based on the subject, if the subject is different then the success is different. That learning is a personality change that is manifested as new patterns. So that learning success can be known from skills, attitudes, habits, knowledge, and skills. So, by developing some of these things it is called learning skills. which is none other than some of the experiences gained because the experience that has been had will be used to connect lessons that are already known with the knowledge to be learned. So that it has a way of solving a problem both now and in the future through systematic steps. A learner who has experience in learning skills can see the problem broadly and can make the right decision. Therefore, students who have experience in learning skills will be better than students with less experience. Thus, in achieving success in learning, experience and skills are needed for students. Experience is a past event that has a great influence and becomes the basis for receiving new experiences.